Pah Pum: A Project Management Tool Based on TAKT PM - Silva, Deyvson; Gomes, Adriano; Macieira, Rafael; Silva, Emanoel; Soares, Sergio (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2020: Anais do XXXIV Simpósio Brasileiro de Engenharia de Software, 2020)
This article presents Pah Pum, a project management tool based on Takt PM, a hybrid project management methodology. The tool was developed at SENAI Institute of Innovation for Information and Communication Technologies to facilitate adherence to Takt PM, offering processes systematization and using best practices suggested by the methodology. The tool supports (1) project planning using a service package diagram called Handoff Network, (2) project monitoring through Kanban and Kanban Quantum boards, (3) automatic Gantt generation and update, according to the project Handoff Network and service packages deliveries, (4) monitoring teams through the observation of a unified board that demonstrates the allocation of the team with the activities that are running or waiting to be performed, (5) automatic allocation of service packages to the teams considering the limit of in progress activities of the team configured to the organization, implementing the pull system, (6) status report of service package delivery and project progress, in a non-declarative way with evidences, and (7) visualization of the project timeline showing the transaction history that includes the project start, service packages deliveries, and service packages rejections that were performed during the project. We used an MVC software architecture to implement the solution, composed by front-end in Vue.js, an API following the REST standard in .Net core, and a SQL Server database. Also, the tool was integrated with the SENAI Technology Management System (a particular ERP system). All modules developed were dockerized and deployed on AWS machines. To access the tool, sign up on https://pahpum.isitics.com, and the administrators will approve the access. We are currently evaluating the tool through a qualitative study to understand the positive and negative impacts through the tool's adoption during the execution of real projects.